(3JMaI GdcQGe HCNHGQ GdHdO GdMQGes - (3eMeO Hf CMeO Hf Ydj, Jbj GdOjf, CHh GdWjH Gdecj GdMSfj,J (B832 (3g` s
(3ChdgG (B:s
(3jHJOF CKfGA GdcdGe Yf eNJUQ cJGH GdYbO GdKejf s
(3BNQgG (B:s
(3jfJgi HbUjOI GdEeGe HOQ GdOjf GHf GdUGMH s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B1150 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B36 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs